2015
DOI: 10.3991/ijet.v10i6.4858
|View full text |Cite
|
Sign up to set email alerts
|

Students’ Perceptions Towards Using Web 2.0 Technologies in Education

Abstract: Abstract-The purpose of this paper is to evaluate the usefulness of Web 2.0 technologies in education. For this purpose, a survey was carried out to explore the students' perceptions towards using these tools for learning purposes. Results of the research study revealed that all the respondents are greatly immersed in these social platforms and use them for many reasons. However, it was found out that almost half of the surveyed students (i.e. 47%) devote more than 40% of the time they spend on Web 2.0 technol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 9 publications
(9 reference statements)
0
15
0
3
Order By: Relevance
“…, at the levels of better academic performance which reflected on higher scores (Lemus-Zúñiga et al, 2015;Mancillas & Brusoe, 2016;Muñoz-Repiso & Tejedor, 2012;Valentín et al, 2013). Students perceptions of regarding the use of ICT on their academic work are positive (Russo, Zhang, & Fallon, 2015), which reflects on the time dedicated to using them to support their academic learning, being approximately half of their time of study (Faizi, Chiheb, & El Afia, 2015), the development of e-skills (Yousseff, 2013). Regarding students with disabilities, the positive aspect of ICT use relates to their social development, although the digital capital depends on the access to technologies and its accessibility (Seale, 2013;Seale, Georgeson, Mamas, & Swain, 2015).…”
Section: B Information and Communication Technologies (Ict)mentioning
confidence: 99%
“…, at the levels of better academic performance which reflected on higher scores (Lemus-Zúñiga et al, 2015;Mancillas & Brusoe, 2016;Muñoz-Repiso & Tejedor, 2012;Valentín et al, 2013). Students perceptions of regarding the use of ICT on their academic work are positive (Russo, Zhang, & Fallon, 2015), which reflects on the time dedicated to using them to support their academic learning, being approximately half of their time of study (Faizi, Chiheb, & El Afia, 2015), the development of e-skills (Yousseff, 2013). Regarding students with disabilities, the positive aspect of ICT use relates to their social development, although the digital capital depends on the access to technologies and its accessibility (Seale, 2013;Seale, Georgeson, Mamas, & Swain, 2015).…”
Section: B Information and Communication Technologies (Ict)mentioning
confidence: 99%
“…Web 2.0 tools are seen as important to eliminate this shortcoming. Butler (2012) defines Web 2.0 as web-based applications that allow users to create content in online environments, which has provided students with some educational advantages such as online discussions and communication via social networks (Faizi, Chiheb, & El Afia, 2015). In addition to these, many benefits of Web 2.0 in facilitating access to information, encouraging collaborative activities and providing low-cost training opportunities were mentioned (Faizi at al., 2015;Grosseck, 2009).…”
Section: Web 20 In Higher Educationmentioning
confidence: 99%
“…The software must provide a new experience to the students, leading them to a more active and collective engagement during the class. Ref [25] confirmed that Web 2.0 technologies are generally associated with a variety of meanings that include an emphasis on user-generated content, information sharing, collaborative efforts, new ways of interacting with Web-based applications as well as the use of the Web as a social platform for creating, repositioning and consuming content. Web 2.0 technologies include social networks, blogs, micro-blogs, wikis, discussion boards, bookmarking and media sharing.…”
Section: The Influence Of the Use Of Technology On Sapmentioning
confidence: 99%